Self Efficacy Of The Elderly After The COVID 19 Vaccine - Dodik Arso Wibowo (Chakra Brahmanda Lentera Institute, 2022)
Background: The Covid-19 vaccine is aimed at the elderly to increase their immunity of the elderly and reduce the significant impact when exposed to Covid-19 at a young age. They are more susceptible to being exposed to the Covid-19 virus. Self-efficacy of the elderly who have received the covid-19 vaccine is better, and the elderly are more confident. Self-efficacy is a person's belief and ability to carry out a form of self-control over the functioning of the individual itself and events in the environment. The purpose of the study was to determine